2011
DOI: 10.1002/cmmi.414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anesthesia carrier gas on in vivo circulation times of ultrasound microbubble contrast agents in rats

Abstract: Purpose Microbubble contrast agents are currently implemented in a variety of both clinical and preclinical ultrasound imaging studies. The therapeutic and diagnostic capabilities of these contrast agents are limited by their short in-vivo lifetimes, and research to lengthen their circulation times is ongoing. In this manuscript, observations are presented from a controlled experiment performed to evaluate differences in circulation times for lipid shelled perfluorocarbon-filled contrast agents circulating wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 39 publications
5
86
0
Order By: Relevance
“…In such methods the quantification of bound tMBs strongly depends on the injected dose, imaging system gain, and local perfusion [137]. In addition, the influence of inhaled gases in the anaesthetic protocols influences the MBs longevity [148][149][150][151]. These studies confirmed longer circulation times of in-house lipid-shell decafluorobutane-filled UCAs and commercially available UCAs such as Definity and Albunex when animals breathe medical air instead of pure oxygen as the carrier gas for the isoflurane anaesthetic.…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 74%
See 1 more Smart Citation
“…In such methods the quantification of bound tMBs strongly depends on the injected dose, imaging system gain, and local perfusion [137]. In addition, the influence of inhaled gases in the anaesthetic protocols influences the MBs longevity [148][149][150][151]. These studies confirmed longer circulation times of in-house lipid-shell decafluorobutane-filled UCAs and commercially available UCAs such as Definity and Albunex when animals breathe medical air instead of pure oxygen as the carrier gas for the isoflurane anaesthetic.…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 74%
“…This is perhaps due to a reduced ventilation/perfusion mismatch and classical diffusion between the blood gases and the gas inside the MBs (e.g. perfluorobutane), in which nitrogen plays a role by increasing the volume of the MBs and diluting other gas species in the MBs gas core [151].…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 99%
“…It is expected that changes in oxygenation and physiology will occur, although we do not anticipate these to dramatically affect microbubble performance [68]. It may, however, influence expression levels, as endoglin is upregulated under hypoxic conditions and is transcriptionally modulated by HIF-1a [32].…”
Section: Discussionmentioning
confidence: 99%
“…Originally developed as ultrasound contrast agents, these micron-sized, lipid-shelled gas bubbles are limited to the vasculature due to their size. They have a relatively short half-life in vivo [5] rendering them insufficiently stable for an entire HIFU surgery, which can last several hours. Nano-sized bubbles are particularly challenging to produce, and exhibit resonance beyond HIFU frequencies.…”
Section: Introductionmentioning
confidence: 99%